Fabrication of hidden portable iron board / Nurul Nasuha Liyana Mohamad Anuar - Mohamad Anuar, Nurul Nasuha Liyana (2022)
Ironing board is a common thing that been used in human daily life especially for tidying up the wrinkled clothes . However, not every iron board can bring it anywhere and easy to store due to its height, width, weight and stiffness when used. This will be a major problem forindividuals, particularly those who live in homes or crowded places with limited space. This project aim to create a iron board with a folding system, generally known as a miniature foldable iron board. This product will be equipped with a folding technology that allow for significant time savings . In addition, making it as a hidden can save spaces.